Alcohol Consumption among Adults in Vietnam: Prevalence, Patterns, and Its Determinants - Santosh Kumar; Mukta Gundi; Sagar Atre; Luu Bich Ngoc; Nguyen Thi Thieng; Anu Rammohan (Institute of Labor Economics (IZA), 2021)
This study describes the prevalence and drinking patterns of alcohol consumption among adults (aged 15+ years) and explores the association between sociodemographic factors and alcohol consumption in Vietnam. A cross-sectional representative survey of 5,200 respondents from 12 provinces was conducted in 2015. Multivariate logistic regression models were fitted to analyze the association between sociodemographic factors (age, gender, education, marital status, income, religion) and alcohol consumption patterns. Nearly three-quarters of males (77%) and one-quarter of females (23%) were current alcohol drinkers. In the multivariate analyses, being male (aOR=10.9, 95%CI = 8.01-14.8, p<0.01), being head of the household (aOR=1.43, 95% CI=1.2-1.8, p<0.01), being married (aOR=1.22, 95%CI=1.1-1.4, p<0.01), having college degree (aOR=1.3, 95% CI=1.07-1.5, p<0.01), higher income (aOR=1.5, 95% CI=1.3-1.6, p<0.001) were positively associated with current drinking. Older respondents (aOR=0.44, 95% CI=0.4-0.6, p<0.01) were less likely to be current users of alcohol. Being male, being household head, marital status, age, and rural residence were negatively associated with consumption of recorded alcohol but were positively associated with consumption of homemade alcohol. High-intake drinking was greater in older age groups and among men. Recorded alcohol was more frequently consumed by younger age groups and in urban areas, while consumption of unrecorded alcohol was higher in rural areas and among low-income households. Targeted policy efforts are needed to reduce the health risk of alcohol consumption among rural and older populations.
Keywords: A10; I1; 330; sociodemographic determinants; homemade alcohol; alcohol use; Vietnam